PERFORMANCE ANALYSIS OF UNIFIED POWER FLOW CONTROLLER (UPFC) USING 3 LEVEL CASADED H BRIDGE (CHB) INVERTERS WITH SPWM AND PI CONTROLLERS - JaganMohan , T. Raju; Ram Das, Prof. G.Tulasi (Innovative Research Thoughts, 2018)
Unified Power Flow Controllers are very much known for their versatality in independently controlling the Active and Reactive Power Flow in a transmission line1 This paper proposes a unique combination of Advanced MLIs like Cascaded H Bridge Inverters in the Converters of UPFCs and a Control Strategies like PI CONTROLLERS for Alleviating the Performance Capabilities of UPFCs. This paper presents the detailed results showing the Improvement in Performance Capabilities of UPFC using the Proposed New Combination of CHB Inverters and Advanced Control Strategy over the Six Pulse Converters. Different Shunt Faults like LG (on Phase A) , LL (on Phases A-B) , LLG (on Phases A - B - Ground) and LLL (on Phases A-B-C) are created at bus number 4 . between bus 3-4 , and the capability of the PI Controller in restoring the system normalcy is also tested. The parameters used for analysing the controller’s performance Settling Time. The test is carried out on a Standard IEEE 5 Bus System. The PWM Technique used is Sine Triangle PWM (SPWM). Simulations pertaining to the entire test procedures are done using MATLAB software.